Prevalence and correlates of orthorexia nervosa in Canadian elite athletes - Ens, G.; Paskevich, D. (2019 SCAPPS Conference. Vancouver, BC, Canada, October 17 -19, 2019, 2019)
Disordered eating attitudes (DEAs) refer to a continuum of abnormal feeding and eating behaviours. The prevalence of DEAs in elite athletes is greater than that of non-athletes, approximately 9% and 4.78% respectively. This is due in part to sport performance demands placedon the athletes (e.g., outcome importance, aesthetic elements, and judging). Researchers have identified "orthorexia nervosa" as an emerging type of DEA which involves a preoccupation with healthful eating, which may be particularly relevant among elite athletes. At present, there is little information regarding who or how many athletes are struggling with a DEA or ON in Canada. The research aimed to determine the prevalence of DEAs and ON in Canadian elite athlete populations. Sex differences, level of competition, and BMI were also examined. Elite Canadian athletes (n = 72) recruited from Canadian Sport Institutes and National Sport Organizations completed questionnaires on eating attitudes. Findings revealed that orthorexic tendencies were observed in 75% of the sample, while DEAs in only 13.9%. No significant associations in symptomatic status were found between sexes X 2(1, 72, 1.858 p= 0.173) or level of competition X2 (1, 72, 0.592, p= 0.442). No significant relationship was found between survey scores and BMI ((F(1,70)= 1.180, p=0.281) r2 =0.017. The prevalence of orthorexic tendencies in this sample is considerably high, particularly compared to global DEAs, and warrants further research to determine clinical significance. Developing prevention and treatment protocol for orthorexic tendencies may contribute to the health and performance of Canada`s elite athletes.